Outcome Prediction by 40-Hz Steady-State Response After Large Hemispheric Infarction - Wang, Yao; Huang, Kaibin; Wang, Shengnan; Wang, Honghao; Ji, Zhong; Pan, Suyue; Wu, Yongming (Frontiers in Neurology, 2018)
Background and Purpose: The 40-Hz steady state response (SSR) reflects early sensory processing and has the potential to differentiate disease severity. This study aims to evaluate the predictive value of 40-Hz SSR on the prognosis of patients with large hemispheric infarction (LHI). Methods: We conducted a retrospective study in patients with LHI admitted to the neurological intensive care unit (NICU) of Nanfang Hospital, Southern Medical University, Guangzhou, China, between June 2008 and December 2014. 40-Hz SSR was recorded within 72 hours of the onset and categorized into 3 grades. The correlation between 40-Hz SSR grading and clinical outcome was examined. Results: Of 97 eligible participants, 41 (42.3%) died within 30 days and 68 (70.1%) ended up with poor outcome (modified Rankin Scale of 5 and 6) at 90 days after the onset of LHI. 40-Hz SSR correlated significantly with NIHSS score at admission and patient outcome. Moreover, 40-Hz SSR Grade III, with bilateral sine waves disappeared or couldn’t be identified clearly, had a specificity of 97% and a positive predictive value of 94% in predicting 90-day poor outcome, and had a specificity of 91% and a positive predictive value of 74% in predicting 30-day mortality. Conclusions: 40-Hz SSR could be used as a simple and specific method in predicting poor prognosis after LHI.